Pharmacokinetics of Intraperitoneal Daptomycin in Patients with Peritoneal Dialysis-Related Peritonitis. Issue 1 (January 2017) - Paul, Laure Peyro Saint; Ficheux, Maxence; Debruyne, Danièle; Loilier, Magalie; Bouvier, Nicolas; Morello, Rémy; Parienti, Jean-Jacques; Verdon, Renaud; Fournel, François; Cattoir, Vincent; Lobbedez, Thierry
Background: Antibiotics are preferentially delivered via the peritoneal route to treat peritoneal dialysis-related peritonitis (PDRP) to ensure that maximal concentrations are delivered to the site of infection. Our study focused on the pharmacokinetics of daptomycin (DAP) administered via the intraperitoneal (IP) route in patients with PDRP. Methods: According to the DaptoDP protocol (Clinical Trial No. 2012-005699-33), IP DAP was administered daily, i.e., during the 6-h Nutrineal (Baxter Healthcare Corporation, Deerfield, IL, USA) dwell time period, for 14 days, in addition to administration of the antibiotics used for the usual care of patients with PDRP. The plasma and IP levels of DAP were measured on days 1 and 5. The tested dose was 200 mg/day. The principal endpoint was the dialysate concentration after 6 hours of dwell time > 16 mg/L (corresponding to 4 x minimum inhibitory concentration [MIC] for E. faecalis ). Results: Three participants were evaluated. On day 5, the IP concentrations after 6 hours of dwell time were between 6.3 and 23.4 mg/L, and the peak plasma concentrations were between 13.0 and 15.3 mg/L. Conclusion: The results suggest that 200 mg/day is very likely sufficient for the treatment of PDRP by Staphylococci or Streptococci whereas it could be insufficient to treat PRDP by Enterococci . The good peritoneal bioavailability of DAP was quantitatively established, suggesting that IP administration could also be used as an alternate route for patients with damaged venous access. No DAP accumulation that could lead to toxic concentrations after repeated administration is expected, even in anuric patients. The protocol will further continue to assess whether a higher dose achieves the pharmacokinetic objectives.